Encyclopedia of Life Sciences 2018
DOI: 10.1002/9780470015902.a0021154.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification

Abstract: The global nitrogen cycle is initiated by the fixation of atmospheric N 2 , by either natural or chemical processes, to bioavailable ammonium (NH 4 + ). Nitrification is the oxidative process that transforms this ammonium to nitrate, via a nitrite intermediate. Nitrification is performed solely by microorganisms: ammonia‐oxidising bacteria and archaea oxidise ammonia to nitrite, nitrite‐oxidising bacteria oxidise nitrite to nitrate and comam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…N 2 O fluxes are likely to occur in MICP due to the abundance of NH4+$$ {{\mathrm{NH}}_4}^{+} $$. N 2 O is a minor product of both nitrification and denitrification (Stein & Nicol, 2018). Ammonia oxidation in quartz sand was observed after 27 days of being in contact with treatment solution (Gat et al, 2016), and a later study indicated an increase in activity of nitrifying bacteria and/or archaea during MICP (Tsesarsky et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…N 2 O fluxes are likely to occur in MICP due to the abundance of NH4+$$ {{\mathrm{NH}}_4}^{+} $$. N 2 O is a minor product of both nitrification and denitrification (Stein & Nicol, 2018). Ammonia oxidation in quartz sand was observed after 27 days of being in contact with treatment solution (Gat et al, 2016), and a later study indicated an increase in activity of nitrifying bacteria and/or archaea during MICP (Tsesarsky et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Organic nitrogen, contained in crop residues and manure, is decomposed and mineralized by the soil microbial communities, resulting in the production of ammonium (NH 4 + ) [5]. During nitrification, which is operated by nitrifying bacteria and involves the oxidation of ammonium to nitrate (NO 3 − ) by key enzymes (e.g., ammonia monooxygenase, hydroxylamine dehydrogenase, nitric oxide oxidase, nitrite oxidoreductase) [6], a small proportion of N is lost as N 2 O. In contrast, denitrification, conducted by denitrifying bacteria, involves the reduction of nitrate and nitrite to gaseous N 2 and N 2 O [7], respectively, by nitrate and nitrite reductases [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrous oxide can be produced through a nitrification-denitrification process that can occur on the abundant inorganic nitrogen in manure. Nitrification occurs aerobically; it converts ammonia into hydroxyl amine via ammonia monooxygenase, hydroxyl amine into nitrite via hydroxylamine oxidoreductase and nitrite into nitrate via nitrite oxidoreductase [ 11 ]. Nitrifiers produce N 2 O during the oxidation of hydroxylamine to nitrite.…”
Section: Introductionmentioning
confidence: 99%